A delay-variation-dependent stability criterion for discrete-time systems via a bivariate quadratic function negative-determination lemma. Issue 10 (July 2022) - Ge, Xiao; Hoi, Kachon; Vong, Seakweng
Abstract: This article concerns with stability analysis of discrete linear systems with time-varying delays. Firstly, we extend a quadratic function negative-determination lemma for a single variable to the bivariate case. Secondly, we construct a novel Lyapunov-Krasovskii functional (LKF) with a quadratically delay-dependent matrix to investigate the stability of discrete-time systems with time-varying delays. Based on the proposed lemma, a new delay-variation-dependent stability criterion is derived. Finally, numerical examples are given to illustrate the theoretical result and the proposed criterion is shown to be less conservative than some previous ones.